Performance measurement system, performance indicators and funding mechanism in Malaysian Public Universities: A conceptual framework. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)

(untitled)
The funding of financial resources in higher education is one of the central issues faced by most governments in the world in this era of competition and globalisation. The public and relevant stakeholders are now closely scrutinising the public universities with what they do, how well they do it and at what cost (Shale and Gomes, 1998).